Hyperthermia as a trigger for Takotsubo syndrome in a rat model - Matthew H. Tranter; Matthew H. Tranter; Bjorn Redfors; Peter T. Wright; Peter T. Wright; Liam S. Couch; Alexander R. Lyon; Elmir Omerovic; Sian E. Harding (Frontiers in Cardiovascular Medicine, 2022)
Takotsubo syndrome is a well-characterized cause of acute yet reversible heart failure associated with periods of intense emotional stress, often mimicking on presentation an acute coronary syndrome. Animal models of Takotsubo syndrome have been developed, either through the application of a stressor, or administration of exogenous catecholamine. We found that in a model of isoproterenol-induced Takotsubo syndrome in anesthetized rats hyperthermia (40–41°C) would occur after the administration of isoproterenol. Maintenance of this hyperthermia would result in an apical hypocontractility typical of the syndrome, whereas prevention of hyperthermia with active cooling to maintain a euthermic core body temperature prevented (but did not subsequently reverse) apical hypocontractility. In vitro experimentation with isolated cardiomyocytes showed no effect of hyperthermia on either baseline contractility or contractility change after beta-adrenoceptor stimulation. We suggest that the rise in body temperature that is characteristic of catecholamine storm may be a component in the development of Takotsubo syndrome.